Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Virome of Solenopsis invicta (Hymenoptera: Formicidae): Intercontinental differences in the native and introduced ranges - Steven M. Valles; Marina S. Ascunce; Quentin D. Read; Roxie L. White; Robert K. Vander Meer (Journal of Invertebrate Pathology, 2025)

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Characterization of macadamia ringspot-associated virus, a novel Orthotospovirus associated with Macadamia integrifolia in South Africa - Ronel Roberts; Nicola Robbertse; Genevieve D. Thompson; David A. Read (European Journal of Plant Pathology, 2024)
South Africa is the largest producer of macadamias in the world, producing an estimated 61,288 tons nut-in-shell in 2022. In order to ensure the sustainability of the industry, it is important that research focuses on the control and eradication of economically important pests and diseases. Macadamia trees in the Mpumalanga Lowveld of South Africa have for some time shown severe chlorosis, which coincides with a significant drop in production, with losses of up to 60% being recorded. The disease has since been coined Macadamia Chlorosis Disease (MCD). In an attempt to determine whether MCD may be associated with a virus, high-throughput Illumina sequencing was performed on RNA extracted from both diseased and healthy trees collected from farms in Mpumalanga. Subsequent data analyses could not link a specific virus to MCD, however, reads spanning the full genome of a novel virus belonging to the Orthotospovirus genus were obtained. An RT-PCR assay was optimized for the detection of this virus and subsequent surveys linked the virus to ringspot symptoms which are commonly observed on different macadamia cultivars. The virus has to date been identified from orchards in Mpumalanga, Limpopo and KwaZulu-Natal. Other viruses described in the genus are known to cause severe crop losses and it is therefore important that the virus, provisionally named macadamia ringspot-associated virus (MRSV), be further studied to determine whether association with this virus can lead to yield losses, and whether appropriate control strategies must be implemented to prevent the spread of MRSV.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

Water-soluble polymers: Emerging contaminants detected, separated and quantified by a novel GPC/MALDI-TOF method - Eve C. Tarring; Isabelle Durance; Michael J. Harbottle; Robert Lucas; Daniel S. Read; Benjamin D. Ward (Environmental Pollution, 2024)

Depositional and tectonic influences on preservation of Milankovitch record during long-term global cooling: Middle and Upper Ordovician convergent foreland, eastern USA - J. Fred Read; Michael C. Pope; Maya Elrick; Linda Hinnov; John Repetski; Robert T. Ryder; Douglas G. Patchen; Richard Diecchio (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

Genomic and phylogenetic characterization of wheat yellows virus, a novel tenuivirus infecting wheat in South Africa - David A. Read; Ronel Roberts; Goddy Prinsloo; Genevieve D. Thompson (Archives of Virology, 2023)

Seasonal gain in body condition of foraging humpback whales along the Western Antarctic Peninsula - K. C. Bierlich; Joshua Hewitt; Robert S. Schick; Logan Pallin; Julian Dale; Ari S. Friedlaender; Fredrik Christiansen; Kate R. Sprogis; Allison H. Dawn; Clara N. Bird; Gregory D. Larsen; Ross Nichols; et al. (Frontiers in Marine Science, 2022)
Most baleen whales are capital breeders that use stored energy acquired on foraging grounds to finance the costs of migration and reproduction on breeding grounds. Body condition reflects past foraging success and can act as a proxy for individual fitness. Hence, monitoring the seasonal gain in body condition of baleen whales while on the foraging grounds can inform how marine mammals support the costs of migration, growth, and reproduction, as well as the nutritional health of the overall population. Here, we use photogrammetry from drone-based imagery to examine how the body condition of humpback whales ( Megaptera novaeangliae ) changed over the foraging season (November to June) along the Western Antarctic Peninsula (WAP) from 2017 to 2019. This population (IWC stock G) is recovering from past whaling and is growing rapidly, providing an opportunity to study how whales store energy in a prey-rich environment. We used a body area index (BAI) to estimate changes in body condition and applied a Bayesian approach to incorporate measurement uncertainty associated with different drone types used for data collection. We used biopsy samples to determine sex and pregnancy status, and a length-based maturity classification to assign reproductive classes ( n = 228; calves = 31, juveniles = 82, lactating females = 31, mature males = 12, mature unknown sex = 56, non-pregnant females = 12, pregnant females = 3, pregnant & lactating females = 1). Average BAI increased linearly over the feeding season for each reproductive class. Lactating females had lower BAI compared to other mature whales late in the season, reflecting the high energetic costs of nursing a calf. Mature males and non-pregnant females had the highest BAI values. Calves and juvenile whales exhibited an increase in BAI but not structural size (body length) over the feeding season. The body length of lactating mothers was positively correlated with the body length of their calves, but no relationship was observed between the BAI of mothers and their calves. Our study establishes a baseline for seasonal changes in the body condition for this humpback whale population, which can help monitor future impacts of disturbance and climate change.

Comparing Uncertainty Associated With 1-, 2-, and 3D Aerial Photogrammetry-Based Body Condition Measurements of Baleen Whales - K. C. Bierlich; Joshua Hewitt; Clara N. Bird; Robert S. Schick; Ari Friedlaender; Leigh G. Torres; Julian Dale; Jeremy Goldbogen; Andrew J. Read; John Calambokidis; David W. Johnston (Frontiers in Marine Science, 2021)
Body condition is a crucial and indicative measure of an animal’s fitness, reflecting overall foraging success, habitat quality, and balance between energy intake and energetic investment toward growth, maintenance, and reproduction. Recently, drone-based photogrammetry has provided new opportunities to obtain body condition estimates of baleen whales in one, two or three dimensions (1D, 2D, and 3D, respectively) – a single width, a projected dorsal surface area, or a body volume measure, respectively. However, no study to date has yet compared variation among these methods and described how measurement uncertainty scales across these dimensions. This associated uncertainty may affect inference derived from these measurements, which can lead to misinterpretation of data, and lack of comparison across body condition measurements restricts comparison of results between studies. Here we develop a Bayesian statistical model using known-sized calibration objects to predict the length and width measurements of unknown-sized objects (e.g., a whale). We use the fitted model to predict and compare uncertainty associated with 1D, 2D, and 3D photogrammetry-based body condition measurements of blue, humpback, and Antarctic minke whales – three species of baleen whales with a range of body sizes. The model outputs a posterior predictive distribution of body condition measurements and allows for the construction of highest posterior density intervals to define measurement uncertainty. We find that uncertainty does not scale linearly across multi-dimensional measurements, with 2D and 3D uncertainty increasing by a factor of 1.45 and 1.76 compared to 1D, respectively. Each standardized body condition measurement is highly correlated with one another, yet 2D body area index (BAI) accounts for potential variation along the body for each species and was the most precise body condition metric. We hope this study will serve as a guide to help researchers select the most appropriate body condition measurement for their purposes and allow them to incorporate photogrammetric uncertainty associated with these measurements which, in turn, will facilitate comparison of results across studies.

Novel viruses associated with plants of the family Amaryllidaceae in South Africa - David A. Read; Ronel Roberts; Dirk Swanevelder; Gerhard Pietersen; Genevieve D. Thompson (Archives of Virology, 2021)

Genomic characterization of two novel viruses infecting Barleria cristata L. from the genera Orthotospovirus and Polerovirus - David A. Read; Ronel Roberts; Genevieve Thompson (Archives of Virology, 2021)

First report of Catharanthus mosaic virus infecting Gomphocarpus physocarpus in South Africa - David A. Read; Ronel Roberts; Genevieve D. Thompson (Journal of Plant Pathology, 2021)

Orchid fleck virus and a novel strain of sweet potato chlorotic stunt virus associated with an ornamental cultivar of Alcea rosea L. in South Africa - David A. Read; Ronel Roberts; Genevieve D. Thompson (European Journal of Plant Pathology, 2021)

Angiosperm symbioses with non‐mycorrhizal fungal partners enhance N acquisition from ancient organic matter in a warming maritime Antarctic - Paul W. Hill; Richard Broughton; Jeremy Bougoure; William Havelange; Kevin K. Newsham; Helen Grant; Daniel V. Murphy; Peta Clode; Soshila Ramayah; Karina A. Marsden; Richard S. Quilliam; Paula Roberts; et al. (Ecology Letters, 2019)
In contrast to the situation in plants inhabiting most of the world’s ecosystems, mycorrhizal fungi are usually absent from roots of the only two native vascular plant species of maritime Antarctica, Deschampsia antarctica and Colobanthus quitensis . Instead, a range of ascomycete fungi, termed dark septate endophytes (DSEs), frequently colonise the roots of these plant species. We demonstrate that colonisation of Antarctic vascular plants by DSEs facilitates not only the acquisition of organic nitrogen as early protein breakdown products, but also as non‐proteinaceous d ‐amino acids and their short peptides, accumulated in slowly‐decomposing organic matter, such as moss peat. Our findings suggest that, in a warming maritime Antarctic, this symbiosis has a key role in accelerating the replacement of formerly dominant moss communities by vascular plants, and in increasing the rate at which ancient carbon stores laid down as moss peat over centuries or millennia are returned to the atmosphere as CO 2 .

Ocean Energy Systems Wave Energy Modelling Task: Modelling, Verification and Validation of Wave Energy Converters - Fabian Wendt; Kim Nielsen; Yi-Hsiang Yu; Harry Bingham; Claes Eskilsson; Morten Kramer; Aurélien Babarit; Tim Bunnik; Ronan Costello; Sarah Crowley; Benjamin Gendron; Giuseppe Giorgi; et al. (Journal of Marine Science and Engineering, 2019)
The International Energy Agency Technology Collaboration Programme for Ocean Energy Systems (OES) initiated the OES Wave Energy Conversion Modelling Task, which focused on the verification and validation of numerical models for simulating wave energy converters (WECs). The long-term goal is to assess the accuracy of and establish confidence in the use of numerical models used in design as well as power performance assessment of WECs. To establish this confidence, the authors used different existing computational modelling tools to simulate given tasks to identify uncertainties related to simulation methodologies: (i) linear potential flow methods; (ii) weakly nonlinear Froude–Krylov methods; and (iii) fully nonlinear methods (fully nonlinear potential flow and Navier–Stokes models). This article summarizes the code-to-code task and code-to-experiment task that have been performed so far in this project, with a focus on investigating the impact of different levels of nonlinearities in the numerical models. Two different WECs were studied and simulated. The first was a heaving semi-submerged sphere, where free-decay tests and both regular and irregular wave cases were investigated in a code-to-code comparison. The second case was a heaving float corresponding to a physical model tested in a wave tank. We considered radiation, diffraction, and regular wave cases and compared quantities, such as the WEC motion, power output and hydrodynamic loading.

Likely annual calving in the vaquita, Phocoena sinus : A new hope? - Barbara L. Taylor; Randall S. Wells; Paula A. Olson; Robert L. Brownell; Frances M. D. Gulland; Andrew J. Read; Francisco J. Valverde‐Esparza; Oscar H. Ortiz‐García; Diego Ruiz‐Sabio; Armando M. Jaramillo‐Legorreta; Edwyna Nieto‐Garcia; Gustavo Cardenas‐Hinojosa; et al. (Marine Mammal Science, 2019)

Characterization and detection of maize-associated pteridovirus (MaPV), infecting maize (Zea mays) in the Arusha region of Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest Mbega (European Journal of Plant Pathology, 2019)

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

Diversity and distribution of Maize-associated totivirus strains from Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest R. Mbega (Virus Genes, 2019)

Molecular characterization of Morogoro maize-associated virus, a nucleorhabdovirus detected in maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherston; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingstone Mashingaidze; Gerhard Pietersen; Barnabas Kiula; Alois Kullaya; Ernest R. Mbega (Archives of Virology, 2019)

First report of maize yellow mosaic virus (MaYMV) on maize (Zea mays) in Tanzania - David Alan Read; Jonathan Featherstone; David Jasper Gilbert Rees; Genevieve Dawn Thompson; Ronel Roberts; Bradley Charles Flett; Kingston Mashingaidze; Dave Kenneth Berger; Tanya Welgemoed; Gerhard Pietersen; Susanna Elizabeth Schulze; Barnabas Kiula; et al. (Journal of Plant Pathology, 2019)

The metabolic regimes of flowing waters - E. S. Bernhardt; J. B. Heffernan; N. B. Grimm; E. H. Stanley; J. W. Harvey; M. Arroita; A. P. Appling; M. J. Cohen; W. H. McDowell; R. O. Hall; J. S. Read; B. J. Roberts; et al. (Limnology and Oceanography, 2018)
The processes and biomass that characterize any ecosystem are fundamentally constrained by the total amount of energy that is either fixed within or delivered across its boundaries. Ultimately, ecosystems may be understood and classified by their rates of total and net productivity and by the seasonal patterns of photosynthesis and respiration. Such understanding is well developed for terrestrial and lentic ecosystems but our understanding of ecosystem phenology has lagged well behind for rivers. The proliferation of reliable and inexpensive sensors for monitoring dissolved oxygen and carbon dioxide is underpinning a revolution in our understanding of the ecosystem energetics of rivers. Here, we synthesize our current understanding of the drivers and constraints on river metabolism, and set out a research agenda aimed at characterizing, classifying and modeling the current and future metabolic regimes of flowing waters.

The role of serotonin in personality inference: tryptophan depletion impairs the identification of neuroticism in the face - Robert Ward; Shubha Sreenivas; Judi Read; Kate E. A. Saunders; Robert D. Rogers (Psychopharmacology, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Rabbit biocontrol and landscape‐scale recovery of threatened desert mammals - Reece D. Pedler; Robert Brandle; John L. Read; Richard Southgate; Peter Bird; Katherine E. Moseby (Conservation Biology, 2016)
Funding for species conservation is insufficient to meet the current challenges facing global biodiversity, yet many programs use expensive single‐species recovery actions and neglect broader management that addresses threatening processes. Arid Australia has the world's worst modern mammalian extinction record, largely attributable to competition from introduced herbivores, particularly European rabbits ( Oryctolagus cuniculus ) and predation by feral cats ( Felis catus ) and foxes ( Vulpes vulpes ). The biological control agent rabbit hemorrhagic disease virus (RHDV) was introduced to Australia in 1995 and resulted in dramatic, widespread rabbit suppression. We compared the area of occupancy and extent of occurrence of 4 extant species of small mammals before and after RHDV outbreak, relative to rainfall, sampling effort, and rabbit and predator populations. Despite low rainfall during the first 14 years after RHDV, 2 native rodents listed by the International Union for Conservation of Nature (IUCN), the dusky hopping‐mouse ( Notomys fuscus ) and plains mouse ( Pseudomys australis ), increased their extent of occurrence by 241–365%. A threatened marsupial micropredator, the crest‐tailed mulgara ( Dasycercus cristicauda ), underwent a 70‐fold increase in extent of occurrence and a 20‐fold increase in area of occupancy. Both bottom‐up and top‐down trophic effects were attributed to RHDV, namely decreased competition for food resources and declines in rabbit‐dependent predators. Based on these sustained increases, these 3 previously threatened species now qualify for threat‐category downgrading on the IUCN Red List. These recoveries are on a scale rarely documented in mammals and give impetus to programs aimed at targeted use of RHDV in Australia, rather than simply employing top‐down threat‐based management of arid ecosystems. Conservation programs that take big‐picture approaches to addressing threatening processes over large spatial scales should be prioritized to maximize return from scarce conservation funding. Further, these should be coupled with long‐term ecological monitoring, a critical tool in detecting and understanding complex ecosystem change.

The contrast sensitivity function of the praying mantis Sphodromantis lineola - Vivek Nityananda; Ghaith Tarawneh; Lisa Jones; Natalie Busby; William Herbert; Robert Davies; Jenny C. A. Read (Journal of Comparative Physiology A, 2015)

Field assessment of C‐ POD performance in detecting echolocation click trains of bottlenose dolphins ( Tursiops truncatus ) - Bethany L. Roberts; Andrew J. Read (Marine Mammal Science, 2015)
We evaluated the performance of dolphin echolocation detectors (C‐ POD s) in the New River, North Carolina, by ground‐truthing echolocation detections with digital acoustic recordings. We deployed C‐ POD s at three sites for a total of 204 monitoring hours. We also performed detection range trials at two sites where water depths ranged from 1.0 to 4.5 m. We used Detection Positive Minutes ( DPM s), minutes of C‐ POD recordings that contained at least one echolocation click train, to indicate the presence of at least one dolphin. The C‐ POD s performed well in detecting dolphin click trains, although all units performed conservatively by failing to detect some echolocation events and therefore underestimated the true occurrence of dolphins. C‐ POD s reported only a small number of false detections, as indicated by low false positive rates ranging between 1% and 4% for individual units. Overall, C‐ POD s performed with a high accuracy (72%–91%) and detected echolocation at a distance of at least 933 m. We conclude that C‐ POD s hold considerable promise in future monitoring studies of this species, but recommend a careful study design especially in complex, coastal environments.

A quantitative analysis of the response of short‐finned pilot whales, Globicephala macrorhynchus , to biopsy sampling - Danielle D. Crain; Ari S. Friedlaender; Dave W. Johnston; Doug P. Nowacek; Bethany L. Roberts; Kim W. Urian; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2014)

Nitrogen-fixing cyanobacteria (free-living and diatom endosymbionts): their use in southern California stream bioassessment - Rosalina Stancheva; Robert G. Sheath; Betsy A. Read; Kimberly D. McArthur; Chrystal Schroepfer; J. Patrick Kociolek; A. Elizabeth Fetscher (Hydrobiologia, 2013)

Biological markers of exposure to organophosphorus nerve agents - Robin M. Black; Robert W. Read (Archives of Toxicology, 2013)

Contrasting responses to water deficits of Nothofagus species from tropical New Guinea and high‐latitude temperate forests: can rainfall regimes constrain latitudinal range? - Jennifer Read; Robert S. Hill; Geoffrey S. Hope (Journal of Biogeography, 2010)
Aim Comparative responses of Nothofagus species to water deficits were studied to determine whether rainfall regimes could limit the latitudinal ranges of tropical and temperate forest species. Location The study species are native to New Guinea, New Caledonia, Australia, New Zealand, Chile and Argentina. Methods Seedlings of Nothofagus species from a broad latitudinal range were grown in a common environment. Changes in conductance, relative water content and water potential were measured in detached shoots, and together with measurements of tissue injury and biomass allocation, were compared between tropical and temperate species. Results Differences in responses to water deficits between tropical and temperate species appear to reflect differences in climate regimes. In particular, species native to ever‐wet rainfall regimes in New Guinea, where water deficits are generally likely to be short‐lived, were effective at conserving water by reduced stomatal conductance. In contrast, high‐latitude evergreen species on average showed greater development of traits that should enhance water uptake. This was particularly evident in Nothofagus cunninghamii from southern Australia, which developed low water potentials at moderate levels of tissue water deficit and higher root:leaf biomass than tropical species, potentially allowing carbon assimilation to be maximized during warmer, but drier, summer months. However, water relations varied among high‐latitude species. In particular, deciduous species on average showed higher rates of conductance, even during moderate levels of tissue water deficit, than evergreen species. Main conclusions The tropical species appear to conserve water during periods of water deficit (relative to temperate species), which is unlikely to have substantial opportunity costs for growth in ever‐wet climates. However, spread of tropical species to higher latitudes may be limited by water conservation strategies that limit carbon gain in climates in which temperature seasonality is often paired with drier summers. Evergreen species from high latitudes, such as N. cunninghamii , commonly showed traits that should increase water uptake. However, this strategy, while probably maximizing growth in temperate climates with cool winters and drier summers, must limit competitiveness at lower latitudes in summer‐wet climates. We conclude that responses to water regimes may make a significant contribution to the latitudinal limits of some evergreen rain forest species.

Biomarkers of organophosphorus nerve agent exposure: comparison of phosphylated butyrylcholinesterase and phosphylated albumin after oxime therapy - Robert W. Read; James R. Riches; Jacqueline A. Stevens; Sarah J. Stubbs; Robin M. Black (Archives of Toxicology, 2010)

Saving the Vaquita: Immediate Action, Not More Data - ARMANDO JARAMILLO‐LEGORRETA; LORENZO ROJAS‐BRACHO; ROBERT L. BROWNELL; ANDREW J. READ; RANDALL R. REEVES; KATHERINE RALLS; BARBARA L. TAYLOR (Conservation Biology, 2007)

Phosphylated tyrosine in albumin as a biomarker of exposure to organophosphorus nerve agents - Nichola H. Williams; John M. Harrison; Robert W. Read; Robin M. Black (Archives of Toxicology, 2007)

The interaction of sarin and soman with plasma proteins: the identification of a novel phosphonylation site - Robin M. Black; John M. Harrison; Robert W. Read (Archives of Toxicology, 1999)